A Durable and Self-Powered Triboelectric Sensor for Hydraulic Pressure Monitoring and Underwater Disturbance Detection - Wang, Weichen; Zhao, Cong; Wang, Zhaoyang; Mao, Baijin; Wang, Haoyu; Zhang, Yiping; Xi, Ziyue; Xiang, Cheng; Xu, Minyi; Qu, Juntian (IEEE sensors journal, 2024)
Enhancing marine sensory capabilities is a crucial pathway to advance human understanding of the oceans. Triboelectric nanogenerators (TENGs), known for their high-quality self-powered sensing properties, present a novel solution for underwater sensing. In this article, we introduce a new hydraulic pressure TENG (HP-TENG) structure designed specifically for HP measurements. When the external HP changes, the slider slides along the cylinder shell and the contact area between the fluorinated ethylene propylene (FEP) film and the aluminum (AI) electrodes changes, thus generating the electrical signal. The electromechanical performance characteristics of the HP-TENG are experimentally measured. Through underwater experiments, we validate the ability of HP-TENG to measure water pressure and demonstrate its ability to perceive the magnitude of pressure and the speed of pressure change with a linear correlation coefficient greater than 0.995. Furthermore, we provide insights into its applications in real-time control and underwater disturbance detection to demonstrate its utility. The sensor has the advantages of low production cost, self-powered, environmentally friendly, high sensitivity to environmental disturbances (0.954 V/N), good mechanical reliability, and electrical stability. The experimental results indicate that the proposed sensor exhibits promising potential for environmental monitoring, emphasizing its utility in enhancing ocean perception for underwater robots.